Miniaturized Dual-Band Dual-Mode Microstrip Patch Antenna with Defected Ground Structure for Wearable Applications - Shamsudin, Nur Azura; Mohd Shah, Shaharil (Journal of Electronic Voltage and Application, 2021)
This work presents the performance of a miniaturized dual-band dual-mode microstrip patch antenna with Defected Ground Structure (DGS) at 2.45 GHz and 5.8 GHz on the stacked substrate configuration in the order of FR-4 â€“ PDMS- FR-4. The antenna offers a promising solution for wearable applications in the ISM bands. The first substrate is a flexible Flame Retardant 4 (FR-4) and the other substrate is a highly flexible Polydimethyl Siloxane (PDMS). The size of the antenna is reduced from 50 Ã— 50 mm2 to 30 Ã— 30 mm2, by introducing DGS on the ground plane. A single U-slot on the rectangular radiating patch is introduced to produce the upper resonant frequency of 5.8 GHz while the existing square patch is to generate the lower resonant frequency of 2.45 GHz. The simulations on the dual-band dual-mode microstrip patch antenna shows the reflection coefficient, S11 at 2.45 GHz is -17.848 dB with a bandwidth of 278.8 MHz and -13.779 dB with a bandwidth of 273 MHz at 5.8 GHz. A unidirectional radiation pattern observed in the E-plane shows that the antenna could be applied for off-body communication while an omnidirectional radiation pattern in the H-plane shows that the antenna can be used for on-body communication. Bending investigation are performed for the antenna over a vacuum cylinder with varying diameters of 50 mm, 60 mm, 70 mm, 80 mm, 90 mm, 100 mm and 120 mm in the CST MWSÂ® software. From the graph of reflection coefficients, the performance of the antenna are not affected in bending condition. The SAR simulations show that the SAR limits obey the guidelines as stipulated by the Federal Communication Commission (FCC) and the International Commission on Non-Ionizing Radiation Protection (ICNIRP) for 1 mW of input power. The 2.45 GHz SAR limit for 1 g of human tissue is 0.09007 W/kg (FCC standard: < 1.6 W/kg) while for  10 g is 0.01867 W/kg (ICNIRP standard: < 2 W/kg). For 5.8 GHz, the SAR limit for 1 g of human tissue is 0.115 W/kg and for 10 g is 0.03517 W/kg.  Based on the performance of the antenna in bending condition and the SAR limits, it is safe to conclude that the antenna can be used for wearable applications at 2.45 GHz and 5.8 GHz of the ISM bands.